The Exportation of the People’s Republic of China’s Surveillance Model: Artificial Intelligence, Social Credit, and its impact on Global Security and Human Rights - Diego Sebastián Sánchez Chumpitaz; Jorge Enrique Abarca Del Carpio (Revista Científica en Ciencias Sociales)
This study examined the consolidation and international expansion of the digital surveillance model promoted by the People’s Republic of China (PRC), built on artificial intelligence (AI) and the Social Credit System (SCS). A mixed-methods approach combined documentary analysis of regulatory frameworks and technologies with quantitative modelling through the State Control Index (SCI), a linear mathematical tool. The SCI assessed the relationship between perceived security, technological deployment, and restrictions on fundamental rights across authoritarian and semi-authoritarian regimes. The findings revealed patterns of authoritarian diffusion via digital infrastructure, interstate agreements, and regulatory transfer. A steady expansion of algorithmic control was observed in fragile institutional contexts, particularly in Latin America, where the security-liberty balance has been historically unstable. In such settings, surveillance systems advanced without solid legal safeguards, reframing citizenship as an object of permanent monitoring and treating dissent as a statistical deviation. This trend undermines individual autonomy and weakens democratic stability.